2021
DOI: 10.1093/police/paaa086
|View full text |Cite
|
Sign up to set email alerts
|

Regular police officer perspectives on the Special Constabulary: An exploratory study

Abstract: A substantial body of research engaging volunteer Special Constables has reflected the importance for them of relationships and integration with their Regular, paid police officer colleagues. This article looks at this professional relationship from the other side, drawing upon 1,382 responses to an online survey of Regular police officers undertaken across five police forces in England and Wales. Findings point to gaps in confidence in the adequacy of recruitment, training, and initial practice competency and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Britton and Knight, 2019), leadership (cf. Britton et al ., 2019a), and career support and development (cf. Ramshaw and Cosgrove, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Britton and Knight, 2019), leadership (cf. Britton et al ., 2019a), and career support and development (cf. Ramshaw and Cosgrove, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Gaston and Alexander (2001: 62) identified almost a quarter of Specials were dissatisfied or very dissatisfied with the training that they had received. Whittle (2014) identified that Special Constables often felt ‘insufficiently prepared’, a sentiment echoed in the study by Prins (2018 :54) who identified that Special Constables ‘spoke passionately about how unprepared their training left them to begin life on the streets as fully warranted officers.’ In addition to the views of Special Constables themselves, Leon (1991) found that 80% of regular officers in her study also felt that the training provided to Special Constables was ‘inadequate’, findings echoed in a later survey-based study of regular officer perspectives of Special Constables (Britton et al, 2021), which found only 16% of regular officers felt that Special Constabulary training was ‘adequate’. Several studies have made the connection between training and the confidence to practice of Special Constables (Bullock and Leeney, 2016; Gaston and Alexander 2001; Prins, 2018; Wolf et al 2016).…”
Section: Introductionmentioning
confidence: 85%
“…Most significantly, the front-line policing activity undertaken by special constables is much more aligned to, and comparable with, that of their regular officer colleagues than had historically been the case. Additionally, recent research has identified that as many as one in six special constables in E&W has a specialist deployment (Britton et al , 2019).…”
Section: Themesmentioning
confidence: 99%
“…A majority of special constables are concentrated on front-line responding, neighborhood policing and visible patrol (Britton and Callender, 2018; Bullock and Leeney, 2016). In a recent national survey of police forces, 1,826 special constables were identified in specialist roles (Britton et al , 2019). Such innovations position special constables within an important space, “resetting relationships with communities and achieving much greater involvement of citizens” (Britton and Callender, 2018, p. 149).…”
Section: Introductionmentioning
confidence: 99%